2022
DOI: 10.1038/s41598-022-11448-6
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable and effective bioprocessing approach for improvement of acid phosphatase production and rock phosphate solubilization by Bacillus haynesii strain ACP1

Abstract: There is indeed a tremendous increase in biotechnological production on a global scale, more and more innovative bioprocesses, therefore, require to perform ideally not only in a small lab- but also on large production scales. Efficient microbial process optimization is a significant challenge when accomplishing a variety of sustainable development and bioengineering application objectives. In Egypt's mines, several distinct types of rock phosphate (RP) are utilized as a source of phosphate fertilizers in agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 34 publications
2
19
1
Order By: Relevance
“…Additionally, the findings from the current investigation indicated that the activated pre-cultures were held at 5% (v/v) inoculum size to produce the most incredible ACP output (41.8 U L −1 ). The ACP production of the B. haynesii strain was found to be maximum at 4.0% (v/v) but reduced as the size of the inoculum rose, according to Abdelgalil et al's [ 13 ] study, which made the same discovery.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Additionally, the findings from the current investigation indicated that the activated pre-cultures were held at 5% (v/v) inoculum size to produce the most incredible ACP output (41.8 U L −1 ). The ACP production of the B. haynesii strain was found to be maximum at 4.0% (v/v) but reduced as the size of the inoculum rose, according to Abdelgalil et al's [ 13 ] study, which made the same discovery.…”
Section: Discussionmentioning
confidence: 79%
“…The results agreed with those obtained earlier by Musarrat et al [ 27 ], who discovered that the optimal pH range for bacteria to dissolve organic P ranged from neutral to moderately acidic. In addition, it was stated by Abdelgalil et al [ 13 ] that an ideal ACP activity peak of 49 U L −1 at pH 7.0 was noted; ACP throughput fell to 47.7 U L −1 at pH 8.0 beyond the optimum pH. Furthermore, the original pH unadjusted media (approximately pH 7.5) produced the most ACP (56.9 U L −1 ) in comparison to the changed media with 1 N HCl (49 U L −1 ) [ 13 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations